Kommunikation und Konfrontation Diplomatie und Gesandtschaftswesen Kaiser Maximilians I. (1486-1519) - Metzig, Gregor (Bibliothek des Deutschen Historischen Instituts in Rom, 2016)
For the first time, the book examines the emergence of the Habsburgs as a leading ruling dynasty under Maximilian I from the perspective of its most important diplomats. It analyzes their influence on European power politics, while also describing their career paths and their role as cultural communicators. This perspective from the field of communication history additionally offers insight into the process of diplomatic exchange during the era.